# Solve for w -2/3w=60

-23w=60
Multiply both sides of the equation by -32.
-32⋅(-23)⋅w=-32⋅60
Simplify both sides of the equation.
Simplify -32⋅(-23)⋅w.
Cancel the common factor of 3.
Move the leading negative in -32 into the numerator.
-32⋅(-23)⋅w=-32⋅60
Move the leading negative in -23 into the numerator.
-32⋅-23⋅w=-32⋅60
Factor 3 out of -3.
3(-1)2⋅-23⋅w=-32⋅60
Cancel the common factor.
3⋅-12⋅-23⋅w=-32⋅60
Rewrite the expression.
-12⋅-2⋅w=-32⋅60
-12⋅-2⋅w=-32⋅60
Cancel the common factor of 2.
Factor 2 out of -2.
-12⋅(2(-1))⋅w=-32⋅60
Cancel the common factor.
-12⋅(2⋅-1)⋅w=-32⋅60
Rewrite the expression.
-1⋅-1⋅w=-32⋅60
-1⋅-1⋅w=-32⋅60
Multiply.
Multiply -1 by -1.
1⋅w=-32⋅60
Multiply w by 1.
w=-32⋅60
w=-32⋅60
w=-32⋅60
Simplify -32⋅60.
Cancel the common factor of 2.
Move the leading negative in -32 into the numerator.
w=-32⋅60
Factor 2 out of 60.
w=-32⋅(2(30))
Cancel the common factor.
w=-32⋅(2⋅30)
Rewrite the expression.
w=-3⋅30
w=-3⋅30
Multiply -3 by 30.
w=-90
w=-90
w=-90
Solve for w -2/3w=60